2020
DOI: 10.2196/15942
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the Role of Analytics in Evaluating Digital Mental Health Interventions for Transition-Aged Youth: Scoping Review

Abstract: Background Consumer-facing digital health interventions provide a promising avenue to bridge gaps in mental health care delivery. To evaluate these interventions, understanding how the target population uses a solution is critical to the overall validity and reliability of the evaluation. As a result, usage data (analytics) can provide a proxy for evaluating the engagement of a solution. However, there is paucity of guidance on how usage data or analytics should be used to assess and evaluate digit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 107 publications
0
16
0
Order By: Relevance
“…It has been suggested that metrics such as high bounce and return visit rates may be too conservative in evaluating the actual impact of eHealth interventions on users ( Paschall et al, 2011 ). As Lo and colleagues (2020) indicate, there does not seem to be a standard as to what constitutes high or low engagement for digital mental health interventions, and there is currently no guidance on how to maximize the value of analytics data.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that metrics such as high bounce and return visit rates may be too conservative in evaluating the actual impact of eHealth interventions on users ( Paschall et al, 2011 ). As Lo and colleagues (2020) indicate, there does not seem to be a standard as to what constitutes high or low engagement for digital mental health interventions, and there is currently no guidance on how to maximize the value of analytics data.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 20 However, in order to meaningfully enable its value, it is expected that effective engagement with the tool is necessary. 17 , 21 23 …”
Section: Introductionmentioning
confidence: 99%
“…Although there is a considerable amount of work that investigates this topic ( Christensen et al, 2009 ; Baumel and Kane, 2018 ; Eysenbach, 2005 ), achieving optimal levels of engagement continues to be a challenge ( Torous et al, 2018 ). Currently, there is lack of a gold-standard definition or established evaluation frameworks for user engagement of mHealth technologies ( Lo et al, 2019 ; Perski et al, 2017 ; Pham et al, 2019a ; Torous et al, 2020 ; Torous et al, 2018 ) which has led to a variability in how usage and engagement are measured. As outlined by Short et al (2018) , there are different methods for measuring user engagement, each offering different advantages and disadvantages in terms of validity and relevance.…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of this study, the definition of user engagement by Perski et al ( Perski et al, 2017 ) will be used: “engagement as using a digital innovation over time”. To our knowledge, few studies look at how TAY uses digital mental health interventions over a significant period of time (i.e., 6 months) ( Lo et al, 2019 ). Thus, evaluating platform usage and engagement of TAY on Thought Spot can be helpful for understanding its potential impact on the outcomes of the Thought Spot RCT ( Pham et al, 2019b ; Pham et al, 2019a ) while also informing how developers can optimize a mental health app for this demographic.…”
Section: Introductionmentioning
confidence: 99%